Schrader's chord - Leeds, Scott (Nightfire, Tor Publishing Group, 2023)
"After his estranged father's mysterious death, Charlie Remick returns to Seattle to help with the funeral. There, he discovers his father left him two parting gifts: the keys to the family record store and a strange black case containing four ancient records that, according to legend, can open a gate to the land of the dead. When Charlie, his sister, and their two friends play the records, they unwittingly open a floodgate of unspeakable horror. As the darkness descends, they are stalked by a relentless, malevolent force and see the dead everywhere they turn.With time running out, the only person who can help them is Charlie's resurrected father, who knows firsthand the awesome power the records have unleashed. But can they close the gate and silence Schrader's Chord before it's too late?"--